ChemInform Abstract: Synthesis of Flavonoids Based Novel Tetrahydropyran Conjugates (Prins Products) and Their Antiproliferative Activity Against Human Cancer Cell Lines. Issue 33 (19th August 2014) - Ahmed, Naseem; Konduru, Naveen Kumar; Ahmad, Sarfaraz; Owais, Mohammad
Abstract A variety of new, highly functionalized flavonoid based tetrahydropyran derivatives are designed, synthesized and evaluated for their antiproliferative activity.